Artificial Intelligence and Medicine 2014-2024: Bibliometric Analysis and Global Impacts - Darıcı, Sefer (Journal of Intelligent Decision Making and Information Science, 2025)
Artificial intelligence (AI) has radically transformed the field of medicine in the last decade, with a significant increase in academic publications. Based on 1783 English-language articles analyzed with Biblioshiny and VOSviewer tools, the findings highlight an annual growth rate of 30.38% and a significant increase from 2018 onwards. Each article received an average of 17.54 citations. The studies had contributions from 11678 authors and an international collaboration rate of 29%. There were single-author (118) and single-country (129) articles. Prominent contributing authors include Forestiero A, Mazzuca D and Zinno F. Harvard Medical School (104 papers) and the University of Toronto (83 papers) have played important roles in the advancement of AI applications in medicine. The USA stands out with both publication volume (3241 articles) and number of citations (9176). Journals such as Journal of Medical Internet Research (26 articles) and Frontiers in Medicine (25 articles) stand out as the leading publication venues in the field. The most cited articles were published in journals such as Jama, Radiology and Nature. This study highlights the wide-ranging applications of AI in areas such as machine learning, deep learning, natural language processing and computer vision, demonstrating its potential in medical imaging, genetic analysis and clinical decision support systems. Future research needs to focus on maintaining collaboration, increasing methodological rigor and finding solutions to emerging challenges.